Genetic diversity for grain nutrients content in finger millet (Eleusine Coracana (L.) Gaertn.) germplasm - Ojulong, H.; Manyasa, E.O.; Patrick, S.; Oduori, C.A.; Adikini, S.; Nyaligwa, L.; Mushoriwa, H.; Solanke, A.U.; Kole, C. (CRC Press, 2023)
Knowledge of existing genetic variability is essential for initiating a successful plant breeding program. This chapter reviews nutrient diversity studies conducted on finger millet germplasm globally. In all the studies, very high variability was observed in all the quality traits determined. Most of the nutrients were positively correlated with each other, implying that they can simultaneously be improved. Grain color and glume covering were associated with nutrient content, with darker grains having higher compared to white-colored and enclosed grains having higher nutrient content than intermediate covered having higher content. These two can be used as morphological markers. Local cultivars and varieties released in the East and South Asia (ESA) region had significantly lower levels of the main essential nutrients (Ca, Fe, and Zn) found in finger millet, most likely as a result of farmers selecting for varieties with brown-colored grain. Country of origin was highly significant for all the nutrients, with accessions from eastern and southern Africa having significantly lower nutrient contents. Grain color was associated with nutrient content with darker grains having higher compared to white colored. All nutrients were positively correlated (P < 0.001) with each other. Grain yield was not significantly correlated with any nutrient content. The substantial variability for the grain nutrients observed in the finger millet core collection and local germplasm indicates the possibility for the selection of nutrient-rich accessions for use in the breeding programs.